Aberrant Origin of Right Hepatic Artery from Superior Mesenteric Artery: A Case Report - Mahajan, A.; Patil, S.; Kakar, S. (New Advances in Medicine and Medical Science Vol. 1, 2023)
The aim of the study was to report the aberrant origin of the hepatic artery from the superior mesentric artery. Understanding the hepatic arterial anatomy is crucial when performing any surgical or diagnostic procedures, including liver transplants. Vascular anomalies are frequently asymptomatic until they affect the viscera's blood supply. They are discovered by chance during surgeries and diagnostic angiography. Variations like this are common in the abdominal vessels. The present case was reported in an adult male cadaver in the Department of Anatomy Maulana Azad Medical College during a routine dissection of the abdomen. The arterial supply of the hepato-biliary system was dissected. The celiac trunk and superior mesenteric artery were identified and branches to the liver identified. The anatomical variations of the hepatic artery can be explained on embryological basis. Each dorsal aorta gives paired ventral splanchnic branches which supply the yolk sac, the primitive gut and its derivatives. The left artery split into three branches that supplied the left lobe of the liver. The right hepatic artery developed from the superior mesenteric artery. Knowledge of variability will help in planning and performing, with less risks of serious ischemic complications, the procurement of donor livers in all its modalities, cadaveric, living, and split livers. This case may be of interest to surgeons and radiologists because distinguishing between the normal arterial pattern and the variant is critical for safe and effective surgery.